(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
It highlights the importance of construction projects because of its significant role in the development of society, including the buildings FEDE projects to their importance to raise the level of education through the conclusion of the special to implementation and the establishment of schools of contracts at the country level, which requires the completion of the project at less time and within the cost specified and the best quality and may highlight the importance of time on all the elements of what has an important role in setting up the project for various reasons may be the need for the use of schools as soon as possible, but the reality showed exceeded the completion of those schools could be up to 6 years and there are some contracts still work which is turned off, which leads to the loss of the project importance and usefulness of Al Society because of the lack of completion on time.